2022
DOI: 10.1109/access.2022.3206364
|View full text |Cite
|
Sign up to set email alerts
|

Connected and Autonomous Vehicle Cohort Speed Control Optimization via Neuroevolution

Abstract: Predictive Energy Management (PrEM) research is at the forefront of modern transportation's energy consumption reduction efforts. The development of PrEM optimization algorithms has been tailored to selfish vehicle operation and implemented in the form of vehicle dynamics and/or adaptive powertrain control functions. With the progress in vehicle automation, this paper focuses on extending PrEM into the realm of a System of Systems (SoS). The proposed approach uses the shared information among Connected and Aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…While not yet as popular as conventional optimum techniques and deep learning, Neuroevolution can easily integrate within control architectures and heuristics to solve complex and system of systems control problems in a simpler manner while enabling adaptive and real-time performance with low compute power, as demonstrated in previous research [16]. Therefore, the Neuroevolution process proposed here is based on previous experience in developing predictive energy management functions for CAV cohorts and vehicles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While not yet as popular as conventional optimum techniques and deep learning, Neuroevolution can easily integrate within control architectures and heuristics to solve complex and system of systems control problems in a simpler manner while enabling adaptive and real-time performance with low compute power, as demonstrated in previous research [16]. Therefore, the Neuroevolution process proposed here is based on previous experience in developing predictive energy management functions for CAV cohorts and vehicles.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, mixing turning and non-turning operations inherently constrains the speed achievable for all vehicles and forces sub-optimal operation. These limitations prompted the authors to investigate the use of Artificial Intelligence, which demonstrated high energy savings with large heterogeneous cohorts operating at controlled intersection [16] and for local powertrain adaptive control [17]. Artificial intelligence offers a simple and fast development framework, low compute power requirements and high reusability thanks to its adaptiveness to a wide range of dynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fuel supply system is composed of pressure regulator components, gasoline pipe components, gasoline pump components, fuel injectors and other components. The electronic control unit feeds back the current working state to the electronic control unit in the form of electrical signal [15][16]. Air intake, fuel injection and ignition control are all control variables of automobile engine idle speed control.…”
Section: Composition Of Automobile Engine Idle Speed Control Systemmentioning
confidence: 99%